Human Resources Management For Improving Medium Small Businesses - Tajeri, Tajeri (International Journal for Educational and Vocational Studies, 2020)
National development is an effort to improve human quality and Indonesian society conducted sustainably. Development the economy originally oriented on industrial industry growth large-scale shifts to more economic development emphasis on democratic economy. one of them through UMKM however lots of small industries that cannot develop wrong one is the rambak crackers industry in Barito Utara because of lack their UMKM ability, so many businesses that go out. With improving the quality of UMKM and the government's role is expected to be to be able to increase entrepreneur's knowledge and skills in terms of technology, facilities and infrastructure, capital and marketing.